Impact of Renewable Electricity Consumption on the Economic Growth of Ecuador. Evidence from the Joint Cointegration Test - Ayaviri-Nina, Víctor Dante; Falconi, Andrés Alejandro Olmedo; Nunez, Alba Isabel Maldonado; Rodriguez, Edgar Anibal (International Journal of Energy Economics and Policy, 2024)
Ecuador has become a benchmark when it comes to sustainable electricity generation in recent years. This research is based on advances in the energy sector, with the aim of knowing the impact of the consumption of renewable electrical energy on economic growth. To carry out the study, annual time series data were used for the period 1990-2021, as well as the unit root tests proposed by Dickey and Fuller in 1981 and Clemente, Montañez and Reyes in 1998. In addition, the proposed by Bayer and Hanck which is the combined cointegration test and the autoregressive distributed lag model (ARDL) to know the impact in the short and long term. Finally, to determine causality, the VECM Granger causality framework was used. The findings demonstrated a positive impact, for every 1% increase in per capita consumption of renewable electrical energy, economic growth will increase by 5.32% in the short term. However, in the long term, for every 1% increase in per capita consumption of renewable electrical energy, economic growth will contract by 0.85%.